Effects of lipopolysaccharide on maturation of bovine oocyte in vitro and its possible mechanisms - Zhao, Shan-Jiang; Pang, Yun-Wei; Zhao, Xue-Ming; Du, Wei-Hua; Hao, Hai-Sheng; Zhu, Hua-Bin (Oncotarget, 2017)
Lipopolysaccharide disturbs the secretion of gonadotropin, endometrial function and implantation efficiency. However, there is little information regarding the effects of lipopolysaccharide on cyclic ovary activity, especially oocyte maturation. Therefore, we aimed to investigate the effects of lipopolysaccharide on the maturation potential of bovine oocytes. We found that lipopolysaccharide exposure significantly decreased the first polar body extrusion rate and delayed the cell cycle progression. The abnormal spindle rate was significantly increased in lipopolysaccharide treatment group, accompanied by disrupted localization and level of phosphorylated mitogen-activated protein kinase (p-MAPK). Moreover, lipopolysaccharide treatment significantly increased intracellular reactive oxygen species (ROS) levels and the early apoptotic rate in oocytes. The pro-apoptotic caspase-3 and Bax mRNA levels and caspase-3 protein level were significantly increased, whereas the anti-apoptotic Bcl-2 and XIAP transcript abundance were significantly decreased in lipopolysaccharide exposure group. Furthermore, the dimethyl-histone H3 lysine 4 (H3K4me2) level was significantly increased, while the DNA methylation (5-mC) and dimethyl-histone H3 lysine 9 (H3K9me2) levels were markedly decreased in oocytes treated with lipopolysaccharide. In conclusion, lipopolysaccharide exposure inhibits the maturation potential of bovine oocytes by affecting cell cycle, cytoskeletal dynamics, oxidative stress, and epigenetic modifications.